Drivers of plant traits that allow survival in wetlands. (21st February 2020) - Pan, Yingji; Cieraad, Ellen; Clarkson, Beverley R.; Colmer, Timothy D.; Pedersen, Ole; Visser, Eric J. W.; Voesenek, Laurentius A. C. J.; van Bodegom, Peter M.
Abstract: Plants have developed a suite of traits to survive the anaerobic and anoxic soil conditions in wetlands. Previous studies on wetland plant adaptive traits have focused mainly on physiological aspects under experimental conditions, or compared the trait expression of the local species pool. Thus, a comprehensive analysis of potential factors driving wetland plant adaptive traits under natural environmental conditions is still missing. In this study, we analysed three important wetland adaptive traits, that is root porosity, root/shoot ratio and underwater photosynthetic rate, to explore driving factors using a newly compiled dataset of wetland plants. Based on 21 studies at 38 sites across different biomes, we found that root porosity was affected by an interaction of temperature and hydrological regime; root:shoot ratio was affected by temperature, precipitation and habitat type; and underwater photosynthetic rate was affected by precipitation and life‐form. This suggests that a variety of driving mechanisms affect the expression of different adaptive traits. The quantitative relationships we observed between the adaptive traits and their driving factors will be a useful reference for future global methane and denitrification modelling studies. Our results also stress that besides the traditionally emphasized hydrological driving factors, other factors at several spatial scales should also be taken into consideration in the context of future functional wetland ecology. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. 摘要: 湿地植物具有能适应缺氧或厌氧湿地生境的特殊功能性状。 关于湿地植物适应性状的研究以前主要集中于实验条件下的生态生理学层面， 或者局限于区域尺度的物种间比较。 迄今仍然缺乏自然条件下的关于湿地植物适应性状驱动因子的综合性研究。 本研究基于新建立的包含来自 21 个研究结果的湿地植物性状数据集， 分析了湿地植物的三种重要适应性状（根孔隙度； 根/茎比例； 水下光合作用速率）的驱动因子。 研究结果表明：根孔隙度主要受温度和水文条件的交互影响； 根/茎比例主要受温度、降水及生境类型的驱动； 水下光合作用速率主要受降水及植物生活型的调节。 且不同的湿地适应性状受不同的驱动机制影响。 本研究所确立的湿地植物适应性状和环境因子之间的定量关系将为未来的全球甲烷模型、脱氮模型等提供重要理论依据。 本研究还提出， 未来的湿地功能生态学不应只局限于传统研究所强调的水文因素， 还应同时考虑不同空间尺度上植物适应性状的各类环境驱动因子。